Tekstens slave: Filemonbrevet som oversættelsesvidenskabelig case - Bergholt, Kasper A. (Dansk Teologisk Tidsskrift, 2025)
This article applies recent translation theories to Paul’s letter to Philemon. Building on an outline of the research history and recent developments within translation studies, I argue that different perspec-tives on translation must be integrated. This means that different aspects (e.g., semantics, history, linguistics, ideology, use, function, and theology) can be emphasized when translating a text resulting in different focuses or mediations of the translation. Furthermore, I present four different translations of selected verses from the letter to Philemon. These translations are then compared and evaluated with regard to their intelligibility and credibility. The conclusion is that although different types of transla-tion may achieve different goals, some translation choices can strengthen or challenge the intelligibility and credibility of a translation.